Analysis of the regional differentiation of the world financial market - Bondarenko, Mikhail; Bunin, Serhii (Technology audit and production reserves, 2018)
The object of research is the global financial market, which unites national financial systems and has significant regional development differentiation. One of the most problematic places for the development of the world market is the reduction of the internal regulatory influence of countries on their financial system as well as the growth of world debt of countries on foreign borrowing, the volatile nature of market development, where the law of uneven economic development manifests itself. The analysis of the dynamics of the global market is used for such indicators as: foreign direct investment and its net outflow (% of GDP); foreign direct investment and its net inflow (% of GDP); the number of national companies listed on the stock exchange and their market capitalization. With the help of classical general scientific research methods, regression analysis, statistical data processing methods, it is obtained that the lowest indicators of capital outflow are inherent in the countries of rapid development (Latin America and the Caribbean, South Asia). The highest rates of capital inflows are inherent in highly developed countries within the European Union or the Eurozone. Most of the companies with quotes on the stock exchange and the largest market capitalization, located in the OECD (Organization for Economic Cooperation and Development), including in the European Union. This is due to the fact that all components of the market are in close relationship. The increase in the volume of monetary savings of the population and free funds of enterprises contributes to the expansion and revitalization of the credit market and the securities market. And the issue of securities reduces the need for financing the economy through loans and accumulates temporarily free funds of investors. This ensures the conditional nature of the separation of financial markets into the money and capital markets.